Maximal number of pre-synaptic ribbons are formed in cochlear region corresponding to middle frequency in mice. (2nd January 2018) - Yang, Le; Chen, DaiShi; Qu, TengFei; Ding, TongHui; Yan, AiHui; Gong, Pinggui; Liu, Yunyi; Zhang, Junjun; Gong, ShuSheng; Yang, ShiMing; Peng, Hong; Liu, Ke
Abstract: Objective: To investigate whether there are more quantitative pre-synaptic ribbons formed in the cochlear region corresponding to middle-frequency in cochlea of mice. Methods: Counts of pre-synaptic ribbons were performed using immunostaining and laser confocal microscopy. Hearing thresholds and function of ribbon synapses were estimated by auditory brain response (ABR) and compound action potential (CAP). Cochlear mapping has been achieved to match the frequencies and corresponding regions along the cochlear spiral. Results: The number of pre-synaptic ribbons in per inner hair cell (IHC) has been found to increase gradually from the base turn, the maximal quantity appeared at the region of 50–70% from the apex. Next, ABR thresholds showed that there was the lowest ABR threshold in the frequency around 8–16 kHz, corresponding to the region of 50–70% from the apex according to the cochlear mapping. Further, CAP amplitudes were estimated, and the maximal value identified at the same frequency (8–16 kHz). Conclusions: Maximal number of pre-synaptic ribbons is formed in the cochlear region of middle frequency in mice, coupling with the lowest ABR threshold and highest CAP amplitudes. Our study shows that the middle frequency (8–16 kHz) could be the most sensitive region to sound stimuli in mice.